2014
DOI: 10.1002/app.41100
|View full text |Cite
|
Sign up to set email alerts
|

Influences of processing on the phase transition and crystallization of polypropylene cast films

Abstract: Phase transition and changes of properties of isotactic polypropylene (i‐PP) cast films with the processing conditions have been investigated by wide‐angle X‐ray diffraction, two‐dimensional small‐angle X‐ray scattering, and atomic force microscopy. It was found that chill roll temperature was a major factor, which influenced the formation of mesomorphic phase and its transition to spherulitic structure. Only mesomorphic phase was observed in the films produced under a chill roll temperature of below 40°C. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…A systematic modelling of the crystallization during processing is desired for understanding the connection between processing and final properties . In detail, a consideration of various structural levels from lamellae to superstructures is necessary here as well, even though films are definitely less complex in this respect than injection molded parts. Generalization has been found to become difficult, when material and processing variations are combined, and this is not yet involving multi‐layer systems resulting from co‐extrusion.…”
Section: Processing‐based Modificationsmentioning
confidence: 99%
“…A systematic modelling of the crystallization during processing is desired for understanding the connection between processing and final properties . In detail, a consideration of various structural levels from lamellae to superstructures is necessary here as well, even though films are definitely less complex in this respect than injection molded parts. Generalization has been found to become difficult, when material and processing variations are combined, and this is not yet involving multi‐layer systems resulting from co‐extrusion.…”
Section: Processing‐based Modificationsmentioning
confidence: 99%
“…23,24 Chatterjee et al reported excellent barrier and optical properties for blown high-density polyethylene (HDPE) lms with optimized draw ratios to achieve special lamellar organization as well as orientation of the amorphous phase. Melt stretching is an effective way to induce chain extension and enhance molecular orientation, thus improving the mechanical properties of polyolens.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of publications on the production of flat polymeric films [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] showed that majority of them are devoted to numerical and experimental modeling of separate stages of their production process. The focus on the process of preparation of polymer melt in the extruder [7][8][9][10], as well as the process of orientation of semi-finished film on the section from the extrusion head to the cooling drum [11][12][13][14][15][16].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Articles [20,21] contain results of research in influence of temperature of the cooling drum on properties of a polypropylene film.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%